Atypical Mycobacterial Infection Arising Amid Corticosteroid Therapy for Livedoid Vasculopathy. (7th October 2019) - Edminister, John R.; Dominiak, Nicole; Gottwald, Lorie D.
Abstract : Patients who suffer from rare skin diseases may try numerous therapies with many potential side effects before achieving remission. Livedoid vasculopathy (LV) is one such rare disease that lacks a definitive treatment as evidenced by randomized controlled trials. Although corticosteroids help reduce the pain flares associated with LV, they come at the risk of immunosuppression. We present a case of disseminated cutaneous infection of M. chelonae/abscessus arising in a diabetic patient on long-term corticosteroid therapy. This patient required an intensive antibiotic regimen and potentially lifelong antibiotic suppression pending improvement of her disseminated cutaneous infection. We report this case to increase awareness of the diagnostic consideration of atypical, rapidly growing mycobacterial (RGM) infection when encountering patients with a diffuse onset of ulcerative skin nodules amid a background of diabetes and long-term corticosteroid use.